DINAMIKA KERUKUNAN UMAT BERAGAMA KOTA AMBON BERBASIS ADAT PERSPEKTIF MASLAHAH - Abdul Muher (TAHKIM, 2018)
The dynamic of religious society peacefulness in Ambon on the base of custom from maslahah perspective has been undoubtedly effective and benefitful to maintain peacefulness and tolerance. Local values such as: a. Ale rasa beta rasa, to feel each other), has been effective in the comtext of tolerance in religious live. These local values are humanity expressions of different religions to share both happiness and bitterness together; b. Katong samua basudara, basicly express men are brothers of one anxious; c. Siwa Lima, to unite Ambonese without differsity), and functionally unite the whole native Ambon-Maluku society and the comers without seeing their religions; d. Pela gandong, which is corresponding Moslems to Moslems, Christians to Christians, and Moslems to Christians).